Improving the Critical Thinking Ability of Vocational High School Students through Digital Teaching Material - Cahyono, Budi Tri; Qodr, Taufiq Subhanul; Budiarto, Mochamad Kamil (LPPM Undiksha, 2024)
Limited variety in mathematics teaching methods can harm student achievement in the subject. Therefore, this research aims to evaluate the impact of using e-books as a learning medium on students' critical thinking abilities. This research applies an experimental approach involving control and experimental groups. This research involved 70 vocational school students who were divided into two groups. The data collection method uses tests. The data collection instrument uses test questions. Data analysis techniques use inferential statistics. Research findings show that using e-books or digital teaching materials significantly improves students' critical thinking abilities. The conclusion that can be drawn is that e-books have proven effective in influencing and improving students' critical thinking abilities. The results of this research underline the great potential of digital learning media, such as e-books, in improving students' critical thinking skills in vocational high school environments. Therefore, it is deemed necessary to widely implement interactive media in e-book format in vocational schools to improve students' critical thinking skills to equip them to face challenges in work and entrepreneurial activities.